2016
DOI: 10.1103/physrevb.93.220503
|View full text |Cite
|
Sign up to set email alerts
|

Read-Green resonances in a topological superconductor coupled to a bath

Abstract: We study a topological superconductor capable of exchanging particles with an environment. This additional interaction breaks particle-number symmetry and can be modelled by means of an integrable Hamiltonian, building on the class of Richardson-Gaudin pairing models. The isolated system supports zero-energy modes at a topological phase transition, which disappear when allowing for particle exchange with an environment. However, it is shown from the exact solution that these still play an important role in sys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(58 citation statements)
references
References 40 publications
2
56
0
Order By: Relevance
“…The conserved operator eigenvalue approach was then extended to accommodate the open case based on results from [8,9,21]. Again, it was found that the result for the ground-state energy is in agreement with mean-field calculations.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The conserved operator eigenvalue approach was then extended to accommodate the open case based on results from [8,9,21]. Again, it was found that the result for the ground-state energy is in agreement with mean-field calculations.…”
Section: Resultsmentioning
confidence: 96%
“…and {T j } is a set of mutually commuting conserved operators. These operators have been shown [9] to satisfy the following quadratic identities…”
Section: The Hamiltonianmentioning
confidence: 99%
“…A common approach, known as the eigenvaluebased method, maps the Richardson-Gaudin equations (3) to an equivalent set of equations for the variables 13,14,25,52,[93][94][95][96][97][98][99]…”
Section: Numericsmentioning
confidence: 99%
“…In particular, the exact Bethe Ansatz solutions provide insight into the topological behaviour of the system through the peculiar behaviour of Bethe roots [7,9,14]. Topological properties of the open model have been studied in [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…This technique was shown to be generalizable in [22,23]. It was subsequently shown for some systems that the conserved operator eigenvalues (COE), satisfying quadratic relations, are inherited from the same relations at the operator level [15,24]. The generalized model considered below also shares this property of underlying conserved operators satisfying quadratic relations [17,18].…”
Section: Introductionmentioning
confidence: 99%